Pengaruh Konsentrasi Atonik Dan Dosis Pupuk Kandang Sapi Terhadap Pertumbuhan Bibit Kelapa Sawit (Elaeis Guineensis Jacq) Sistem Prenursery - Komang Suta Darmawan; I Gusti Bagus Udayana; A.A. Ngurah Mayun Wirajaya; Made Sri Yuliartini (GEMA AGRO, 2020)
This study entitled "Effect of Atonic Concentration Doses and Cow Manure Dose on Growth of Oil Palm Seedlings (Elaeis guineensis Jacq.) Prenursery System". This study aims to determine the interaction and influence of atonic concentrations and doses of cow manure on oil palm nurseries (Elaeis guineensis Jacq.) In the prenursery system. This research was conducted at the Experimental Station of the Faculty of Agriculture, University of Warmadewa, with a height of 25 meters above sea level, which was carried out on 17 February 2019 to 18 May 2019. This research used a Randomized Block Design (RBD) with factorial patterns. The treatments that were tried consisted of two factors, namely: The first factor of atonic concentration consisted of: Z0: (Control), Z1: (Concentration of 1 cc l-1), Z2: (Concentration of 2 cc l-1), and Z3: (Concentration 3 cc l-1). The second factor is cow manure (P0) which consists of: P0: (Control), P1: (Cow Manure 15 g / polybag), P2: (Cow Manure 30 g / polybag), and P3: (Cow Manure 45 g / polybag). Thus there are 16 combinations of treatments. Each was repeated 3 times, so there were 48 oil palm seed trial units. Based on this research can be several things as follows : Research shows that the interaction between atonic concentrations and doses of cow manure on all variables observed has no significant effect. The treatment of atonic concentrations of 2 cc l-1 gave the highest average dry weight of the leaf oven at 2.87 g, an increase of 48.70% when compared with the lowest yield at the control atonic concentration of 0 cc l-1 at 1.93 g. The treatment of cow manure doses showed that in the nursery of the oil palm prenursery system all the observed variables had no significant effect.